Refine Energy Efficiency in LTE Networks: A Proposal for Reducing Energy Consumption through NFV and SDN Optimization - Nabil Abdulwahab Baban (Journal of Engineering Research and Reviews)
With the rapid proliferation of mobile data traffic and the expansion of Long-Term Evolution (LTE) networks, energy consumption has become a significant concern for telecom operators and service providers. Current LTE infrastructure, designed for optimal performance, often disregards the energy efficiency of network operations, leading to increased operational costs and environmental impact. This paper deals with the issue of energy wastage that is abundant in LTE networks through the alliance of Network Function Virtualization (NFV) and Software-Defined Networking (SDN) technologies. NFV and SDN have been concentrated on enlarging network flexibility and lessening delay; however, there has not been much consideration given to their power to boost energy efficiency. The fundamental problem that will be covered in this paper is high power consumption, which is tied to regular LTE networks that are inflexible and demand many resources. One of the principal contributions of this paper is the development of an innovative optimization model that effectively addresses 4G technologies by integrating Network Functions Virtualization (NFV) and Software-Defined Networking (SDN). This model is designed to provision network resources, scale network functions, and facilitate intelligent traffic routing. It possesses the capability to dynamically modify network configurations in real-time based on current traffic conditions, thereby minimizing energy consumption while maintaining an acceptable level of Quality of Service (QoS). The proposed design employs multi-objective optimization techniques aimed at reducing energy usage and achieving a balance among various parameters related to network performance. The framework is validated using simulation scenarios that compare energy consumption and network performance between traditional and proposed models. The results prove that the proposed NFV-SDN integrated model is highly energy efficient, with network performance equal to or better than before. This paper proposes an innovative technique for the reduction of energy consumption in LTE networks towards environmentally sustainable and cost-effective management of the next-generation mobile network. [J Eng Res Rev 2025; 2(1.000): 22-47]